Empowering Stroke Survivors: developing a patient version of guidelines to facilitate patient rehabilitation nursing of stroke patients with limb dysfunction in China - Dan Yang; Jingyuan Zhang; Meiqi Meng; Xuejing Li; Lijiao Yan; Jiaxin Fang; Ziyan Wang; Sihan Chen; Xiaoyan Zhang; Yufang Hao; Fang Wang (Frontiers in Public Health)
ObjectiveTo develop a patient version of guidelines (PVG) for rehabilitation nursing (RN) in stroke patients with limb dysfunction, aiming to enhance patients’ awareness, self-management skills, and adherence to rehabilitation programs.MethodsThis guideline was developed based on the cultural and healthcare context of China, and was guided on the Minimum standards for the Development Process, Content and Governance of Patient-Directed Knowledge Tools and the PVG tool book of the Guidelines International Network. The guideline was constructed through a normative process involving clarifying priority questions, assessing and integrating evidence, detailing and contextualizing recommendations, and evaluating the prototype of PVG.ResultsFifteen priority RN issues were identified, and eight articles (four guidelines and four evidence summaries) were included, all demonstrating robust methodological quality. The final guideline encompassed five themes: disease knowledge, functional assessment, symptom prevention and nursing, rehabilitation training, and traditional Chinese medicine nursing - a specialized approach integrating traditional Chinese medicine principles with modern nursing practices, including 26 recommendations.ConclusionThis patient-centered guideline, grounded in a robust scientific framework and tailored to patient needs, serves as a valuable reference for the RN of stroke patients with limb dysfunction. The development of context-specific patient guidelines that integrate best available evidence remains an area requiring continued effort and refinement. Further research is warranted to evaluate the implementation and effectiveness of this guideline within diverse Chinese healthcare context.